Supply Chain Conceptual Model in Logistic Operation Strategies for Best Practice Performance - Abi Anwar, Umari Abdurrahim; Wirayudha, Aditia; Suwarsi, Sri; Anuar, Azyyati; Mohamed, Baderisang (KnE Social Sciences, 2023)
Business actors, ranging from national to global levels, seek to capitalize on competitive advantages, and modern supply chains often adopt a globally distributed manufacturing system by outsourcing logistics processes to service providers. In the FMCG (Fast- Moving Consumer Goods) industry, companies must effectively control the supply chain through the establishment of a robust logistics and SCM (Supply Chain Management) management system. This study aims to analyze and describe an efficient logistics management model in the FMCG industry to enhance company performance. The research employs a qualitative descriptive method, utilizing a narrative literature study and conducting case studies on FMCG companies in Indonesia. The study’s findings demonstrate that building and implementing an effective logistics model, particularly through the integration of information technology, service quality, and communication, along with optimizing delivery methods, can significantly improve company performance in the FMCG industry. Moreover, the study highlights the impact of commitment and trust on loyalty, attitudes, and behavior concerning logistics management within the FMCG sector. Keywords: business, FMCG, logistics, operations management, supply chain management